Therapeutic interventions to urologic chronic pelvic pain syndrome and UPOINT system for clinical phenotyping: How far are we?. Issue 3 (August 2022) - Naveed, Muhammad; Changxing, Li; Ihsan, Awais Ullah; Shumzaid, Muhammad; Kamboh, Asghar Ali; Mirjat, Ali Asghar; saeed, Muhammad; Baig, Mirza Muhammad Faran Ashraf; Zubair, Hafiz Muhammad; Noreen, Sobia; Madni, Asadullah; Xiaohui, Zhou
The assessment and management of urologic chronic pelvic pain syndrome (UCPPS), is controversial. It is classified by voiding symptoms, pelvic pain, and bladder pain, which is weekly treated, weekly understood, and bothersome. In the aspect of clinical efforts and research to help people with this syndrome have been hampered by the deficiency of a widely reliable, accepted, and a valuable tool to evaluate the patient symptoms and quality of life (QoL) impact. However, the etiology comes into sight is multifactorial, and available treatment options have been imprecise considerably in present years. We compiled the published literature on the assessment of the syndrome, a tentative role of pharmacological and non-pharmacological (conservative, alternative, and invasive therapy) interventions in eradicating the disease as well as improving symptoms. The previously published literature on animal models has established the association of immune systems in the etiology, pathogenesis, and progression of the disease. The UPOINT system for clinical phenotyping of UCPPS patients has six predefined domains that direct multimodal therapy, which would lead to significant symptom improvement in the medical field. The narrative review aims to scrutinize the fluctuating scientist's views on the evaluation of patient and multimodal treatment of the UPOINT system.